Organic waste compost and spent mushroom compost as potential growing media components for the sustainable production of microgreens - Poudel, Pradip; Duenas, Anela E. K.; Di Gioia, Francesco (Frontiers in Plant Science, 2023)
Microgreens are emerging specialty crops becoming increasingly popular for their rich nutrient profile and variety of colors, flavors, and textures. The growing medium is a significant key factor in microgreen yield, quality, and sustainability. The widespread use of peat-based media raises questions regarding the environmental sustainability of microgreens production, and new substrates that are more sustainable are required. To this purpose, a study was designed with the objective of comparing eight alternative growing media evaluating their physicochemical properties and effect on yield, mineral profile, and nutritional quality of peas and radish microgreens. Tested substrates included a standard peat and perlite mixture (PP), coconut coir (CC), spent mushroom compost (SMC), organic waste compost (CMP), and 50:50 (v:v) mixes of PP and SMC, PP and CMP, CC and SMC, and CC and CMP. The physicochemical properties widely differed among the alternative substrates tested. SMC had high electrical conductivity and salt concentration, which resulted in poor seed germination. Growing media tested significantly influenced the production and nutritional quality of both microgreen species and variations were modulated by the species. With a 39.8% fresh yield increase or a small yield decrease (-14.9%) in radish and peas, respectively, PP+CMP (50:50, v/v) mix provided microgreens of similar or higher nutritional quality than PP, suggesting the potential of substituting at least in part peat with CPM. Using locally available CMP in mix with PP could reduce the microgreens industry reliance on peat while reducing costs and improving the sustainability of the production of microgreens. Further research is needed to evaluate also the potential economic and environmental benefits of using locally available organic materials like CMP as alternative growing media and peat-substitute to produce microgreens.